2013
DOI: 10.1371/journal.pone.0064619
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Cytokines Protect Retinal Pigment Epithelial Cells from Oxidative Stress-Induced Death

Abstract: PurposeTo investigate the effects of inflammatory factors and oxidative stress on cell survival of the human retinal pigment epithelial (RPE) cell line, ARPE-19.MethodsConfluent RPE cells were treated with peripheral blood mononuclear cells-conditioned medium (PCM), H2O2, NaIO3, interferon (IFN)-γ, tumor necrosis factor (TNF)-α, or combinations of these. Cell viability was determined by viability assays and by light microscopy. Effector molecules of cell death were investigated by immunofluorescence microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 69 publications
0
29
0
Order By: Relevance
“…Hence, previous data have shown a clear association between RPE health and compromised mitochondrial function. High numbers of mitochondria are present in metabolically active cells like the RPE while their number decreases with age, particularly in AMD [33-35]. Experimental findings have also shown a link between mitochondrial impairment and RPE degeneration, which would arise as a consequence of an in-balance of the cellular redox system.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, previous data have shown a clear association between RPE health and compromised mitochondrial function. High numbers of mitochondria are present in metabolically active cells like the RPE while their number decreases with age, particularly in AMD [33-35]. Experimental findings have also shown a link between mitochondrial impairment and RPE degeneration, which would arise as a consequence of an in-balance of the cellular redox system.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the increased expressions of inflammation-related proteins (complement factor C3 and calcium-independent phospholipase A2)252627, pro-angiogenic factor (IL-8)14, chemoattractant (stromal cell-derived factor-1)25, oxidative stress-related gene (heme oxygenase)26 as well as apoptotic marker (caspase-3)28 have been reported. Apart from induction of RPE cell death, sodium iodate would also cause mitochondrial dysfunction and impairment of glycolysis1629. In addition, disruption of blood-retina barrier has been indicated in sodium iodate-treated mice3031.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, sodium iodate induces necrosis in primary mouse RPE cells with decreased expression of necrostatin-1 (Nec-1)15. In addition, acute sodium iodate-induced ARPE-19 cell death is associated with mitochondrial dysfunction and p62 upregulation16. While the acute effects of sodium iodate treatment on RPE cells are extensively studied, the effects of a prolonged exposure and the dosage effect of sodium iodate on culture of RPE cells have not been investigated yet.…”
mentioning
confidence: 99%
“…A recent study demonstrated that inflammatory cytokines protect against oxidative stress induced degeneration of the RPE (Chen et al, 2013; Juel et al, 2013). TLR3 signaling within astrocytes leads to secretion of neuroprotective mediators and promotes tissue repair responses (Bsibsi et al, 2006).…”
Section: Discussionmentioning
confidence: 99%